What Is Known and Not Known About Palestinian Intifada Terrorism:: The Criteria for Success - Chasdi, Richard (Journal of Conflict Studies, 2007)
Abstract This article employs three "success criteria" – Dimensionality, Temporality, and Locus of Success – to assess the achievements of Palestinian terrorism during the al-Aqsa Intifada. Dimensionality refers to recognizable manifestations of recognition (political-social success), organization, and military achievement. Temporality gauges the achievements of terrorist campaigns or sets of events on a time continuum: the long haul, the medium term, and the short run. Locus of success addresses the basic question: success for whom? In the period prior to the First Intifada, Palestinian terrorism achieved recognition but little else apart from strengthening the Palestinian-Arab terrorist organizations politically and financially, in part at the expense of broader-based Palestinian-Arab „insider‟ interests. The First Intifada presents a somewhat different picture than the earlier period. In the case of dimensionality, recognition of the legitimacy of the Palestinian struggle was enhanced and there was rapid expansion of organizational structures but the military success criterion remained underdeveloped. The single, most significant achievement of the First Intifada at the organizational level may have been the development of internal infrastructure in the Occupied Territories with an enormous capacity to keep a general movement thriving in an effective and sustained way. The al-Aqsa Intifada presents a different picture. First, by showing that they were willing to kill and be killed for the sake of the movement, it illuminated the depth of the Palestinians‟ commitment. Second, the Palestinians‟ resort to terrorist attacks on Israeli settlements and into Israel proper during the second Intifada, and especially the increasing use of „suicide bombers,‟ represented a profound and lasting change in strategy from the „limited force‟ approach that characterized the first uprising. These attacks generated and sustained fear among Israelis which, in turn, increased pressure on the political elite for political change. Perhaps the single, most significant success in this respect was the removal of Israeli settlers from the Gaza Strip in 2005. However, the al-Aqsa Intifada does not seem to have achieved any other macro-political goals, such as serious reconsideration on the part of the Israeli elite of the status of the West Bank, including Jerusalem. Nor has it solved the familiar set of Palestinian-Arab internal problems that include corruption and the development of aspects of „civil society.‟ A key question is what to do with Hamas, the group which is now the de facto „government‟ of Gaza but is simply not committed to the notion of a „two state solution.‟ Finally, the al-Aaqsa Intifada highlights the transition of the national liberation struggle from a condition of successes and failures to the point where the emerging reality is a nation-state-in-the-making that comes complete with a system of „representative democracy,‟ including independent institutions that thrive in effective and sustained ways.